Reappraisal of the Prostaglandin E1 Dose for Early Newborns with Patent Ductus Arteriosus-Dependent Pulmonary Circulation - Fu-Kuei Huang; Chu-Chuan Lin; Ta-Cheng Huang; Ken-Pen Weng; Po-Yen Liu; Ying-Yao Chen; Hsiao-Ping Wang; Luo-Ping Ger; Kai-Sheng Hsieh (Pediatrics and Neonatology)
The usual initial dose of prostaglandin E1 (PGE1) for ductal-dependent congenital heart disease (CHD) is 50–100 ng/kg/minute. The aim of this study was to review our experience of a low initial dose of PGE1 treatment in early newborns with congenital heart disease and patent ductus arteriosus (PDA)-dependent pulmonary flow. Methods: We reviewed the clinical data of 33 newborns with CHD and PDA-dependent pulmonary circulation who were admitted from January 2005 to December 2010. Clinical parameters were collected, including, PGE1 dosage, oxygenation condition, vital signs, and other related clinical parameters during admission. Echocardiography was employed to assess the status of the PDA as clinically indicated. Results: Thirty-three newborns, including 17 males and 16 females, with CHD and PDA-dependent pulmonary circulation were enrolled in the study. Their mean age was 2.9 ± 5.1 (within the range of 1–26) days with a median of 1.0 day. Among the 33 cases, 25 were diagnosed with pulmonary atresia and eight with critical pulmonary stenosis. Twenty-five of our patients were treated with the initial low-dosage regimen of 20.0 ± 7.4 ng/kg/minute in our neonatal intensive care unit. None of these 25 patients with had significant apnea necessitating intubation and none had hypotension, fever, convulsion or cortical hyperostosis. Three of the eight patients who were treated with high-dose PGE1 (39 ± 13.2 ng/kg/minute) before referral to our unit had apnea and intubation after PGE1 use. All patients had adequate PDA patency with a low maintenance dose of 10.5 ± 5.3 ng/kg/minute before operation under our protocol. Conclusion: In our experience, adequate PDA flows in early newborns with CHD and PDA-dependent pulmonary circulation could be achieved at a much lower dose than recommended in the literature. The lower dose of PGE1 also causes much fewer complications, such as apnea, fever, and hypotension. For early newborns with CHD and PDA-dependent pulmonary circulation, treatment with a lower initial dose of PGE1 of 20 ng/kg/minute and a maintenance dose of 10 ng/kg/minute is recommended.